Pomen prostora in časa v Driadi Gregorja Strniše - Žunkovič, Igor (Slavica Tergestina, 2015)
The article analyses the space/time construction of reality in Driada, one of Gregor Strniša's most unusual works. The drama does not follow the aristotelian rules of the three unities. Furthermore, it easily changes between different historical periods and places and therefore constructs a virtual reality, which exists behind what can be seen through limited human experience of the world. The transitions from the biggest to the smallest and from the past to the future are distinguished features ot the grotesque image of reality. The grotesqe character of the play gives rise to an ethic dimension, which sees the contradiction between the poetic comprehension of the world and its everyday consumer logic.
Keywords: čas; poetic drama; poetična drama; prostor; Slovene drama; Slovene literature; Slovene writers; slovenska dramatika; slovenska književnost; slovenski pesniki; space; time